Use of a MAIT Activating Ligand, 5-OP-RU, as a Mucosal Adjuvant in a Murine Model of Vibrio cholerae O1 Vaccination - Owen Jensen; Shubhanshi Trivedi; Kelin Li; Jeffrey Aubé; J. Scott Hale; Edward T. Ryan; Daniel T Leung (Pathogens and Immunity, 2022)
Background: Mucosal-associated invariant T (MAIT) cells are innate-like T cells enriched in the mucosa with capacity for B-cell help. We hypothesize that targeting MAIT cells, using a MAIT-activating ligand as an adjuvant, could improve mucosal vaccine responses to bacterial pathogens such as Vibrio cholerae.